(untitled) (Annals of Medical Research, 2023)
Aim: Hashimoto’s thyroiditis (HT) is a common chronic autoimmune thyroid disease. Many studies on autoimmune diseases have investigated human cathelicidin from the anti-microbial peptide family. This article aims to determine the level of cathelicidin in Hashimoto’s thyroiditis and evaluate its relationship with thyroid functions. Materials and Methods: Eighty-eight subjects were included in the study. Gender, age, and BMI were similar between 48 HT patients and 40 healthy controls. Cathelicidin levels were studied in serum samples with an ELISA kit. Results: There were euthyroid and subclinical hypothyroid HTs in the study. There was a significant difference between the controls and patients in terms of TSH (p<0.001), fT4 (p=0.001), anti-TPO (p=0.001), and anti-Tg (p=0.001). Median cathelicidin level was significantly higher in the HT group (853.53 pg/ml) than in the control group (577.08 pg/ml) (p<0.001). Cathelicidin levels were similar (p=0.555) in HT with euthyroid and subclinical hypothyroidism. There were no correlations between cathelicidin level and age, year of disease, BMI, TSH, fT4, fT3, anti-TG, and anti-TPO. Diagnosis of HT was approximately 5.6 times higher in patients with high cathelicidin values ​​(p<0.001). The possible effect of cathelicidin on the development of HT was evaluated by univariate binary logistic regression analysis, and the diagnostic threshold for cathelicidin was found to be 714 pg/ml (sensitivity 71%, specificity 70%). Conclusion: Our study is the first to examine the relationship between HT and serum cathelicidin. High cathelicidin was associated with HT independent of thyroid hormone levels, a possible role in the pathogenesis of HT.